The social care component of multidisciplinary mental health teams: a review and national survey - Chris Baker (Journal of Health Services Research & Policy, 2012)
BackgroundThe study reviewed the disciplinary composition of community mental health teams (CMHTs) and conducted a national survey of mental health providers in England and Wales to explore the determinants of the social care component and of CMHTs. MethodsA comprehensive literature review and a national survey of NHS mental health Trusts in England and Wales.ResultsThe literature review showed that team composition was rarely well justified with regard to effectiveness, despite some evidence that greater professional diversity (i.e. inclusion of social workers) was associated with higher effectiveness. Forty-two mental health Trusts responded (53.2%) to the survey. There were no staffing differences between responding and non-responding Trusts. Social workers accounted for 19.3% of the staffing total. Nurses formed a third of the workforce and social support workers made up a further 10%. Social workers bring a different perspective to CMHT work. We found that there continues to be a shortage (compared to policy targets and previous research) of psychiatrists, psychologists and occupational therapists, whereas the numbers of nurses employed far exceeds their target numbers.Total staffing numbers appeared to be slightly higher in Trusts citing ‘financial resources’ as a determining factor of team composition. Despite being statistically non-significant, the ‘financial resource’ effect was of medium magnitude. Similarly, there was a non-significant but approaching medium-sized effect of higher numbers of social care support staff when guidance was cited as a rationale for CMHT composition. There was a non-significant (p=0.076) medium magnitude (2p=0.067) trend towards higher staff numbers in more integrated trusts that did not cite financial resources as a driver of team composition.ConclusionsIf service recipients are to gain equal access to appropriately staffed services, further attention needs to be paid to supporting an adequately skilled multidisciplinary workforce. The workforce needs to be organised in a way that best provides for local needs rather than a service based largely on the existing supply of different professionals and disjointed workforce planning.